The Influence of Equal-Channel Angular Pressing on the Microstructure and Properties of a Steel–Aluminum Composite - Yang Liu; Junrui Xu; Bingnan Chen; Yuqi Fan; Wenxin Lv; Hua Sun (Metals)
Under the global initiative for automotive lightweighting to address climate challenges, this study investigates the microstructure evolution of steel–aluminum composites processed by hot equal-channel angular pressing (H-ECAP). Using 6061-T6 aluminum cores clad with 20 # low carbon steel tubes processed through 1–4 C-path passes (Φ = 120°, ψ = 30°), we demonstrate significant microstructural improvements. The steel component showed progressive grain refinement from 2.2 μm (1 pass) to 1.3 μm (4 pass), with substructures decreasing from 72.19% to 35.46%, HAGB increasing from 31.2% to 34.6%, and hardness increasing from 222 HV to 271 HV. Concurrently, aluminum experienced grain refinement from 59.3 μm to 28.2 μm, with recrystallized structures surging from 0.97% to 71.81%, HAGB increasing from 9.96% to 63.76%, and hardness increasing from 51.4 HV to 83.6 HV. The interfacial layer thickness reduced by 74% (29.98 μm to 7.78 μm) with decreasing oxygen content, containing FeAl3, Fe2Al5, and minimal matrix oxides. Yield strength gradually increased from 361 MPa (one pass) to 372.35 MPa (four passes), accompanied by a significant enhancement in compressive strength. These findings reveal that H-ECAP’s thermomechanical coupling effect effectively enhances interface bonding quality while suppressing detrimental intermetallic growth, providing a viable solution to overcome traditional manufacturing limitations in steel–aluminum composite applications for sustainable mobility.